Analisis Kesalahan Fonologi Pada Teks Deskripsi Kelas VII SMP 12 Tasikmalaya - Resti Nurbiadu Intani; Syakira Fauziah; Marwatul Kamilah; Ai Siti Nurjamilah (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This study aims to analyze the errors in descriptive texts of class VII students of SMP 12 Jakarta. This study is a descriptive qualitative type. The research instrument is the researcher himself. The data collection technique used is documentation study. The source of indicator data is the choice of words and sentences. The data is then analyzed with preliminary steps then continued to the method, results and discussion and closed with conclusions and suggestions. Based on the results of the descriptive text written by class VII students of SMP 12 Jakarta, several errors were found in writing so that the sentences used were ineffective. The most common error found was an error in phonemes.